Applicability of XRD/Rietveld Analysis with an External Standard Method for the Quantification of Mineral Components in Carbonated Hardened Cement Paste - Saeki, Naohiko; Kurihara, Ryo; Maruyama, Ippei (Journal of Advanced Concrete Technology, 2024)
For the quantification of mineralogical components in cementitious materials using XRD, the external standard method, where the standard material is measured separately from the samples, has several advantages in avoiding artifacts arising from internally mixing the standard material. This method has been applied to the quantification of cement clinker and its hydration process, but rarely to its carbonation progress. In this study, we examined its applicability to carbonated cement pastes. By determining the H2O and CO2 amount contained in each sample, the mass attenuation coefficient was calculated, which enabled quantification using the external standard method. Four different standard materials were examined, among which α-corundum was regarded as the most crystalline, and hence, most suitable. Comparing the obtained quantitative amounts of portlandite and calcium carbonate with those in the TG results and the calcium aluminate phases with those in 27Al NMR results, we demonstrated that the external standard method can accurately quantify the crystalline amount. Additionally, it was shown that the choice of the crystal structure of vaterite for Rietveld refinement has a significant influence on the quantification in Rietveld refinement.